Righting Resource-Curse Wrongs in Uganda: The Case of Oil Discovery and the Management of Popular Expectations - Kiiza, Julius; Bategeka, Lawrence; Ssewanyana, Sarah (Economic Policy Research Centre (EPRC), 2011)
This paper discusses the management of expectations associated with the recent discovery of commercializable oil in Uganda. Our motivation is simultaneously theoretical and pragmatic. Theoretically, resource abundance oftentimes begets a natural resource-curse, that is, the tendency for resource-rich countries to attain poorer developmental outcomes than resourcepoor countries (Auty, 1993; Collier et al, 2004). Practically, oil development in Uganda appears set to create winners and losers. Four categories of winners are spelt out in Uganda’s Oil and Gas Policy – the central government; the oil companies; the district local governments of the oilrich areas; and the land owners. The oil-rich lands have not been nationalized to make all Ugandans winners. Bunyoro-Kitara Kingdom (hereafter: ‘Bunyoro Kingdom’) also complains that it has been left out. Yet, it has a historical and cultural claim over the oil-rich lands. Sections of the local community, whose environment could be contaminated by oil-spills, are also concerned that no context-specific environmental safeguards have been developed.
Keywords: Resource-Curse Wrongs; Oil Discovery; Management